On iterative equivalence of some classes of mappings - Jachymski, Jacek (Annales Mathematicae Silesianae, 1999)
We introduce the notion of iterative equivalence of two classes of mappings on metric spaces and we demonstrate its utility in metric fixed-point theory. In particular, we show that the fixed-point theorem for Matkowski's contractions can be derived from the corresponding theorem for Browder's contractions, though the first class of mappings is essentially wider than the second one.